Desenvolvimento de um estetoscópio digital de baixo custo - RIBEIRO, Flávia de Cássia Martins (2025)
The use of a digital stethoscope is a new development the way we observe cardiac rhythms. One of the primordial tools used by doctors since the 19th century, the stethoscope is used in patient diagnosis to principally identify cardiovascular diseases. In this case, this work presents research and tests developed for the creation of a digital stethoscope prototype. The chapters in this project outline the concepts of acoustics, human physiology, stethoscope function, and other fundamental topics necessary to the development of this project. Also, there are concepts presented on the topics of signal processing and, noise filtering, microphone eletreto function, transducer development for audial signals. For the amplification and signal pre-processing, a circuit with an operational amplifier was used. A Programmable System on a Chip (PSoC) was developed in order to adjust for the desired audial cardiac signal range, which was the focus of the project. All the process for signal acquisition, processing, and filtering, along with circuit prototyping as well as the following tests and results propitiate to a discussion involving the importance of this technology in the medical field, were developed throughout this work.